Mercadores de sentidos: a comunicação de vendedores ambulantes com estrangeiros por meio da intercompreensão multilíngue - Ferreira, Léo de Sousa (2010)
This paper aims, starting with the studies of languages in contact and communicative competence, to locate and describe the interlanguage, a linguistic phenomenon observed in the interaction between beach sellers and foreign tourists. We seek to discover whether those interacting use some kind of pidgin, or some code as a lingua franca. We also seek to identify the manner in which the features of communicative competence are presented by analyzing the various competences that composes it - linguistic, sociolinguistic, pragmatic and psycholinguistic. The analysis of speech acts, the maxims and conversational implicatures given in the corpus were important to verify whether those interacting were successful in their attempt at multilingual intercomprehension.